Pengaruh kombinasi konsentrasi giberelin (ga3) dan lama perendaman terhadap perkecambahan benih salak bongkok (salacca edulis r.) - endeh masnenah; Sari Hayati; Roni Assafaat Hadi; Lia Amalia (COMPOSITE : Jurnal Ilmu Pertanian, 2026)
Germination of Snake Fruit seeds takes a long time? because have thick and hard skin. One effort to overcome was to soak the seeds used gibberellin (GA3). The aim of research was to determine the effect of the combination of gibberellin (GA3) concentration and soaking time to germination of snakefruit seeds. This experiment was conducted at the Screenhouse of the Horticultural Seed Center UPTD, Jatinangor, Sumedang at an altitude of 800 meters above sea level, from April to June 2024. The experimental method used a Randomized Block Design (RBD) with 7 combination treatments of gibberellin (GA3) concentration and soaking time consisted of A (0 mg.L-1 GA3, 24 hours); B (30 mg.L-1 GA3, 12 hours); C (30 mg.L-1 GA3, 24 hours); D (60 mg.L-1 GA3, 12 hours); E (60 mg.L-1 GA3, 24 hours); F (90 mg.L-1 GA3, 12 hours); and G (90 mg.L-1 GA3, 24 hours)), each repeated 4 times. The results showed that the combination of gibberellin (GA3) concentration and soaking time affected on seed germination power, germination speed, seed height, number of leaves and root volume. The combination of gibberellin (GA3) concentration and soaking time of 30 mg.L-1 GA3, 24 hours (C), gave the best effect on seed germination power, germination speed and seed height. Treatment G (90 mg.L-1 GA3, 24 hours) and F (90 mg.L-1 GA3, 12 hours) gave the best effect on the number of leaves and root volume of salak bongkok.